2016
DOI: 10.1002/mus.25465
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue reduction during aggregated and distributed sequential stimulation

Abstract: SEQ techniques hold promise for reducing fatigue during NMES-based rehabilitation and exercise; however, optimization is required to improve efficiency. Muscle Nerve 56: 271-281, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 60 publications
0
33
0
Order By: Relevance
“…Stimulation on the muscle belly activates localized muscle fibres around the electrodes, while nerve trunk stimulation activates muscle fibres evenly in the entire muscle belly [ 13 ]. Moreover, since muscle belly stimulation activates localized muscle fibres around the electrodes, repeated stimulation can also induce muscle fatigue [ 12 , 81 ].…”
Section: Electrical Stimulation Of Muscles and Nervesmentioning
confidence: 99%
“…Stimulation on the muscle belly activates localized muscle fibres around the electrodes, while nerve trunk stimulation activates muscle fibres evenly in the entire muscle belly [ 13 ]. Moreover, since muscle belly stimulation activates localized muscle fibres around the electrodes, repeated stimulation can also induce muscle fatigue [ 12 , 81 ].…”
Section: Electrical Stimulation Of Muscles and Nervesmentioning
confidence: 99%
“…Yet excessively high stimulus frequencies can also promote rapid fatigue (Naess and Storm-Mathisen 1955, Jones et al 1979, Metzger and Fitts 1986, Jones 1996, McDonnall et al 2004). Therefore, some FES investigators have turned to asynchronous stimulation (Lind and Petrofsky 1978, Yoshida and Horch 1993, Wise et al 2001, McDonnall et al 2004, Malešević et al 2010, Nguyen et al 2011, Maneski et al 2013, Sayenko et al 2014, Downey et al 2015, Bergquist et al 2016, 2017, Laubacher et al 2017, Lou et al 2017), an approach originally described by Rack and Westbury (1969), wherein different sets of motor units are activated sequentially at relatively low rates using multiple electrodes. Such asynchronous (or interleaved stimulation) can produce reasonably smooth muscle force despite low stimulus rates delivered to each set of motor units that, on their own, would cause markedly unfused contractions (Rack and Westbury 1969, Wise et al 2001, Sandercock 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Although the fatigability of SES and sequential stimulation was previously compared during dynamic contractions [47], [48], these experiments are the first to compare the fatigability of the tibialis anterior muscle contractions during SES and SDSS under isokinetic conditions. Previous studies from our group and others have shown that sequential stimulation produces isometric muscle contractions that are more fatigue-resistant than SES in the quadriceps [3], [5], [10], [12], triceps surae [2]- [5], biceps femoris [3], [5] and tibialis anterior [3]. Sayenko et al [3] showed that SDSS was 51% more fatigue-resistant than SES during isometric contractions, which is in line with the results reported here where SDSS produced 56% less fatigue than SES during isokinetic contractions.…”
Section: Fatigabilitymentioning
confidence: 87%
“…To minimize the premature fatigue associated with SES, researchers have developed a technique involving "sequential" rotation of stimulation pulses between multiple active (cathode) electrodes positioned over a muscle belly or a group of muscle bellies [2]- [5], [10]- [13]. Sequential stimulation (also referred as asynchronous [13], rotary [14], distributed [12], [15], [16] or interleaved [17]- [19]) crudely mimics the asynchronous pattern and firing frequency range of motor unit recruitment associated with voluntary contractions [20].…”
mentioning
confidence: 99%